HUBUNGANPEMBERIAN IMUNISASI BACILLE CALMETTE GUERIN (BCG) TERHADAP FAKTOR KEJADIAN TUBERCULOSIS (TB) PARU BALITA DI KLINIK DEGRITHA BANJARBARU - Sari Wahyunita; Eny Hastuti; Arif Fauzi (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2020)
Pulmonary tuberculosis is an infectious disease caused by the bacterium Mycobacterium Tuberculosis by transmission through patients when coughing or sneezing in the form of droplets. The data of DepKes RI (2018) prevalention of tuberculosis in South Kalimantan there are 210 cases (10.08%). One effort to reduce the prevalence of tuberculosis in infants and children is BCG immunization. The study aimed to determine the relationship of BCG immunization to the incidence of pulmonary tuberculosis in Banjarbaru Degritha Clinic. The research method by observasional deskriptive analysis with cross-sectional approach. The result of this research was shown the incidence number of pulmonary tuberculosis in Banjarbaru Degritha Clinic against the group with given BCG immunization as 7 people (16.3%) while the group with not given BCG immunization as 40 people (93%). The Chi-Square test results show a significant relationship between BCG immunization and the incidence of pulmonary tuberculosis in Banjarbaru Degritha Clinic.